Analysis of tactical, decisional and executional behaviour according to the level of expertise in squash - Catalán-Eslava, M.; González-Villora, S.; Pastor-Vicedo, J. C.; Contreras-Jordán, O. R. (Journal of Human Kinetics, 2018)
The objective of this study was to analyse the differences in tactical principles, decision-making and execution of the return shot and drop shot of squash players at different levels of proficiency. The sample was composed of 80 players, divided into four levels of expertise (first national category, second national category, autonomous regional level and provincial level). The Squash Performance Evaluation Tool was used for recording the level of decision-making and execution. The results revealed that reading of the context of the game improved as the level of the player`s expertise of both the return shot and the drop shot increased. The correlation between correct decision-making and better quality execution for both the return shot and the drop shot in squash also improved with the player`s level of expertise. According to these results, improvements in situational tactical principles and the application of tactical principles, correct decision-making and high-quality execution are essential to develop the athletic performance level among squash players.